PERSSEPSI SISWA TERHADAP LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 1 MALAUSAM - Fitriani, Dede; Asiyah, Dewi (LPPM UNU CIREBON, 2024)
This research is entitled Student Perceptions of Guidance and Counseling Services at SMPN 1 Malausma, Majalengka Regency. The problem in this study is that the role of the counselor in Guidance and Counseling in schools is seen as a special teacher for students who have problems and still sticks with most students. Students perceive that every student who is called into the Guidance and Counseling room is a problem student. The purpose of this study is to explain students' perceptions of good and correct Guidance and Counseling services in schools. The method used by the guidance and counseling teacher and the efforts made by the guidance and counseling teacher in providing an understanding of Guidance and Counseling services to students of SMPN 1 Malausma, Majalengka Regency. The method used in this research is descriptive method with a qualitative approach, while the data collection techniques used in this study are observation, interviews, and documentation, with the research subjects being students of SMPN 1 Malausma, Majalengka Regency. The results showed that students' perceptions of Guidance and Counseling services students assumed that the guidance and counseling teacher was often angry (negative) and thought that the counseling teacher gave directions to students who had problems (positive), this was due to the level of counseling services to students The low one.